2015
DOI: 10.1112/s1461157015000054
|View full text |Cite
|
Sign up to set email alerts
|

Champ: a Cherednik algebraMagmapackage

Abstract: We present a computer algebra package based on Magma for performing computations in rational Cherednik algebras with arbitrary parameters and in Verma modules for restricted rational Cherednik algebras. Part of this package is a new general Las Vegas algorithm for computing the head and the constituents of a module with simple head in characteristic zero, which we develop here theoretically. This algorithm is very successful when applied to Verma modules for restricted rational Cherednik algebras and it allows… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…The Hilbert series of any finitedimensional Nichols algebra also satisfies this symmetry. The following question for rational Cherednik algebras was posed by Thiel in [37, Question 7.7(a)] and [38,Problem 6.6]; nevertheless some restrictions are required because he also gives counter-examples in the first paper, see [37,Remark 7.8]. In this situation Theorem 2.1 gives us information on the projective u (H,R) (V )modules:…”
Section: On the Representation Theory Of U (Hr) (V )mentioning
confidence: 99%
“…The Hilbert series of any finitedimensional Nichols algebra also satisfies this symmetry. The following question for rational Cherednik algebras was posed by Thiel in [37, Question 7.7(a)] and [38,Problem 6.6]; nevertheless some restrictions are required because he also gives counter-examples in the first paper, see [37,Remark 7.8]. In this situation Theorem 2.1 gives us information on the projective u (H,R) (V )modules:…”
Section: On the Representation Theory Of U (Hr) (V )mentioning
confidence: 99%
“…In [73] the author has explicitly computed the solutions to all Problems in Section 2.6 for G 4 and for all parameters using computational methods. In [71] we have shown that for precisely the groups With much more computational effort we have determined in [73] the complete solutions to all problems in Section 2.6 for generic parameters for the groups G 4 , G 5 , G 6 , G 7 , G 8 , G 9 , G 10 , G 12 , G 13 , G 14 , G 15 , G 16 , G 20 , G 22 , G 23 = H 3 , G 24 .…”
Section: Exceptional Groupsmentioning
confidence: 99%
“…We refer to [16] for the details. All results computed so far are available on the author's websites http://www.mathematik.uni-stuttgart.de/~thiel/RRCA and http://thielul.github.io/CHAMP On the latter website the Cherednik Algebra Magma Package CHAMP presented by the author in [73] is freely available. This is a package based on the computer algebra system Magma for performing basic computations in rational Cherednik algebras at arbitrary parameters and in baby Verma modules for restricted rational Cherednik algebras.…”
Section: Exceptional Groupsmentioning
confidence: 99%
“…This technique has been extended by Geck and Rouquier [14] to a decent class of algebras over integral domains. It became an important tool for studying algebras involving parameters, so for example Hecke algebras (see [13], [12], and [7]) and, more recently, rational Cherednik algebras (see [2], [15], and [28]). We list several further examples in §2A.…”
Section: Introductionmentioning
confidence: 99%